Soil moisture sensor - RUNGE THOMAS H; HILL JASON LESTER; ZIMMERMAN JAMES (2015)
In one embodiment, the present invention is directed to a soil moisture sensor for interrupting an irrigation schedule of an irrigation controller. The moisture sensor comprises a relatively flat body with two lower electrodes and two lower anchoring barbs. A receiver receives moisture readings from the sensor and compares moisture data to a predetermined moisture interrupt value or limit, over which irrigation is interrupted.